The resource hazards model for the critical infrastructure of the state emergency management process - Teresa Ostrowska (Foundations of Management, 2013)
This paper presents an investigation of the relevant factors related to the construction of a resource model which is designed to be useful in the management processes of the operation of critical infrastructure (CI) for state emergencies. The genesis of the research lay in the perceived need for effective protection of multidimensional CI methodologies, and it was influenced by the nature of the physical characteristics of the available resources. It was necessary to establish a clear structure and well defined objectives and to assess the functional and structural resources required, as well as the potential relational susceptibilities deriving from a number of possible threats and the possible seriousness of a specific range of incidents and their possible consequences. The interdependence of CI stocks is shown by the use of tables of resource classes. The dynamics of the interaction of CI resources are modeled by examining how using clusters of potential risks can at any given time create a class of compounds related to susceptibilities and threats to the resources. As a result, the model can be used to conduct multi-dimensional risk calculations for crisis management CI resource configurations.
Keywords: 650; resource; resource features; class of resources; threats and susceptibilities of the class of resource; critical infrastructure system (CI system); positioning resources of CI; hazards cluster